Canonical and Non-canonical Inflammasome Activation by Outer Membrane Vesicles Derived From Bordetella pertussis - Elizagaray, Maia L.; Gomes, Marco Túlio R.; Guimaraes, Erika S.; Rumbo, Martín; Hozbor, Daniela F.; Oliveira, Sergio C.; Moreno, Griselda (Frontiers in Immunology, 2020)
Outer Membrane Vesicles (OMVs) derived from different Gram-negative bacteria have been proposed as an attractive vaccine platform because of their own immunogenic adjuvant properties. Pertussis or whooping cough is a highly contagious vaccine-preventable respiratory disease that resurged during the last decades in many countries. In response to epidemiologic situation new, have been incorporated boosters into the vaccination schedules and new vaccine candidates have started to be designed. Particularly, our group designed a new pertussis vaccine candidate based on OMVs derived from Bordetella pertussis (BpOMVs). To continue with the characterization of the immune response induced by our OMV based vaccine candidate, in this work we investigate the ability of OMVs to activate the inflammasome pathway in macrophages. We observed that NLRP3, caspase-1/11 and gasdermin-D (GSDMD) are involved in inflammasome activation by BpOMVs. Moreover, we demonstrated that BpOMVs as well as transfected B. pertussis lipooligosaccharide (BpLOS) induce caspase-11 (Casp11) and guanylate-binding proteins (GBPs) dependent non-canonical inflammasome activation. Our results elucidate the mechanism by which BpOMVs trigger one central pathway of the innate response activation that is expected to skew the adaptive immune response elicited by BpOMVs vaccination.